Adsorption optimization of acyclovir on prepared activated carbon. (7th August 2014) - Jain, Swati; Kumar, Pardeep; Vyas, Raj K.; Pandit, Prabhat; Dalai, Ajay K.
<x xml:space="preserve">Abstract</x> Canadian pine cones (pine cone type I and pine cone type II) and deoiled canola meal were utilized as precursors for preparation of powdered activated carbons (PACs) using thermo‐chemical process. Physicochemical properties of the biomass and obtained adsorbents were evaluated. Prepared PACs were investigated for the adsorptive removal of acyclovir (ACV) from aqueous solutions. Pine cone type I PAC was found to have well developed pores and surface area. It was found to be suitable for removal of ACV from aqueous solution. Response surface methodology was used for the optimization of ACV adsorption on PAC prepared from pine cone type I and the development of predictive model. A second‐order polynomial equation fitted data well which indicated that the process variables such as temperature, pH and especially adsorbent dose had large impact on the ACV adsorption process. The optimum conditions for ACV removal were found to be 39 °C, pH 8 and 2 g/L of pine cone type I PAC dose. At these conditions, the removal of ACV was 90.3 %, which was close to the maximum predicted value of 92.5 %.